Abusive Supervision: A Systematic Review and New Research Approaches - Gallegos, Ivonne; Guàrdia-Olmos, Joan; Berger, Rita (Frontiers in Communication, 2022)
Abusive leaders affect employees’ emotions and health and produce counterproductive behaviors that cause economic damage to organizations. The literature has focused predominantly on the antecedents of abusive supervision and its negative impact, providing knowledge on mechanisms that link abusive supervision to consequences for subordinates. There has been limited research on the supervisor perspective, on the group level and on recovery. This review makes three contributions: first, we examine the theoretical approaches used by previous research to understand abusive supervision. Second, we analyze the types of mechanisms that explain how and when abusive supervision process occurs. Third, we identify and discuss applied methodologies and limitations. Based on the preferred reporting items for systematic reviews and meta-analysis guidelines, and transactional well-being process perspective, analyzed 171 empirical manuscripts and 239 samples between 2010 and July 2020. We identified a growth in abusive supervision research between 2018 to 2020 and found 101 different theories. Most of these theories view abusive supervision from a social, relational, or affective perspective but seldom from an emotional perspective. We classified four types of mechanisms: simple relations between abusive supervision and antecedents-consequences (12), moderators (47), mediators (26), and a combination of mediators and moderators (86). We found research has mostly been performed at the employee level or on dyads; studies that analyze the team level are rarely found. We identified two methodological problems: cross-sectional designs, which do not allow the analysis of its causality. Another problem is the increased risk of common method variance that may influence the results obtained via single-source data. In conclusion, the theories used have focused on employee perceptions, which has not enabled the broadening of the abusive supervision concept to include the supervisor’s perspective and a recovery-related perspective. Research on how and when abusive supervision occurs analyzed with complex mechanisms using emotional variables and appropriate daily methodologies has been scarce. We propose a theoretical expansion including emotional theories to uncover emotional consequences of abusive supervision and the recovery concept to provide a deeper insight into abusive supervision process. We contend that longitudinal and diary designs that include teams and supervisor levels are necessary.